Neuro-, cardio-, and immunoplasticity effects of early adversity. - Pakulak, Eric.; Steven, Courtney; Neville, Helen
The relationship between early adversity and outcomes across the lifespan is apparent in a striking range of measures. Evidence suggests that many of these outcomes can be traced to the impacts of early adversity on multiple and integrated biological systems mediated by the brain. In this review, we integrate empirical and theoretical advances in the understanding of relationships among the brain and the functions of the endocrine, autonomic, and immune systems. We emphasize the effects of environmental experiences related to caregiver relationships because it is these experiences, in particular, that shape regulatory and threat response systems in ways that increase vulnerability and may underlie the wide range of poor outcomes associated with early adversity. Thus, we metaphorically extend the concept of plasticity to highlight our goal of a broader consideration of these interconnected mechanisms. We conclude by discussing implications for neurobiologically informed interventions that can potentially ameliorate the broad and costly effects of early adversity. -- (from the author)
Keywords: Neuroplasticity; Early adversity; HPA axis; Autonomic nervous system; Immune system